Penyuluhan Terapi Progressive Muscle Relaxation (PMR) Terhadap Penurunan Tekanan Darah Primenopause di Puskesmas Lubuk Kilangan - Yulita, Defi; Intani, Trya Mia (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Hypertension is commonly known as a slow killer. According to data from the World Health Organization (WHO), in 2020, 1.56 billion adults suffered from hypertension. Hypertension can be managed pharmacologically and non-pharmacologically. One non-pharmacological treatment that can reduce blood pressure is Progressive Muscle Relaxation (PMR) therapy. This community service activity aims to increase premenopausal women's knowledge about Progressive Muscle Relaxation (PMR) therapy for lowering blood pressure. This program was implemented in the Lubuk Kilangan Community Health Center on July 26, 2024, through counseling and demonstrations of Progressive Muscle Relaxation (PMR) therapy for perimenopausal women. Based on the results of the counseling and demonstration activities, 80% of perimenopausal women were able to practice Progressive Muscle Relaxation (PMR). It is hoped that through this activity, perimenopausal women will be able to perform Progressive Muscle Relaxation (PMR) therapy regularly every day.